Food choices and practices during pregnancy of immigrant women with high-risk pregnancies in Canada: a pilot study - Higginbottom, Gina M.A.; Valliantos, Helen; Forgeron, Joan; Gibbons, Donna; Mamede, Fabiana; Bariola, Rubina (BioMed Central, 2014)
Background: Immigrant women may be regarded as a vulnerable population with respect to access and navigation of maternity care services. They may encounter difficulties when accessing culturally safe and appropriate maternity care, which may be further exacerbated by language difficulties and discriminatory practices or attitudes. The project aimed to understand ethnocultural food and health practices and how these intersect in a particular social context of cultural adaptation and adjustment in order to improve the care-giving capacities of health practitioners working in multicultural perinatal clinics.